Metabolite shifts induced by marathon race competition differ between athletes based on level of fitness and performance: a substudy of the enzy-magIC study - Schader, Jana F.; Haid, Mark; Cecil, Alexander; Schoenfeld, Julia; Halle, Martin; Pfeufer, Arne; Prehn, Cornelia; Adamski, Jerzy; Nieman, David C.; Scherr, Johannes (Metabolites, 2020)
This study compared metabolite shifts induced by training for, participation in, and recovery from a marathon race competition among athletes divided into three groups based on fitness (relative maximum oxygen uptake (VO2max)) and performance levels (net running time). Plasma samples from 76 male runners participating in the Munich Marathon were analyzed for metabolite shifts using a targeted metabolomics panel. For the entire cohort of runners, pronounced increases were measured immediately after the race for plasma concentrations of acylcarnitines (AC), the ratio (palmitoylcarnitine + stearoylcarnitine)/free carnitine that is used as a proxy for the activity of the mitochondrial enzyme carnitine palmitoyltransferase, and arginine-related metabolites, with decreases in most amino acids (AA) and phospholipids. Plasma levels of AA and phospholipids were strongly increased 24 and 72 h post-race. Post-race plasma concentrations of AC and arginine-related metabolites were higher in the low compared to top performers, indicating an accumulation of fatty acids and a reliance on protein catabolism to provide energy after the marathon event. This study showed that marathon race competition is associated with an extensive and prolonged perturbation in plasma metabolite concentrations with a strong AC signature that is greater in the slower, less aerobically fit runners. Furthermore, changes in the arginine-related metabolites were observed.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Amino acids; Biomarker; Exercise; Fatty acids; Metabolism; Urea cycle